THE EFFECT OF ECRI, NPF AND BI RATE UPON MARGIN REVENUE OF MURABAHAH AT BMT ALGHAZALY YEAR 2012 - 2016 - Rizki Ahmad Fauzi (The Accounting Journal of Binaniaga, 2017)
The main task of finance institutions is to collect and distribute the financing and Baitul Mal Tamwil or BMT is one of the financing institutions that is collecting the financing from the clients’ capital and savings. Financing distribution is to give the debtors the loan. Most financing support given is Murabahah . Murabahah is a financial support given thru a trading principle where handing over the ownership has happened. The profit is calculated in advance and as a part of the price of the goods sold. Determining the profit rate of murabahah financing support has been influenced by many factors. But, the writer is going to pick three factors only, they are an Expected Competitive Return For Investor (ECRI), Non Performing Financing (NPF) and Bank of Indonesia (BI) rate. Logically, BMT board of directors should have to determine the amount of selling price of murabahah financing support which is based on ECRI and BMT should have given a certain amount which is the remaining of the business revenue to the investor. However, a risk cost has to be anticipated supposing the debtors cannot afford to pay their loans. And the third variable is BI rate as a considerate reference to evaluate whether the profit of murabahah financing support is competitive in the market or not. Ensuring whether ECRI, NPF and BI rate have been affecting murabahah revenue or not, the writer has applied quantitative method and primary data from the direct key persons. The result of the research has identified that simultaneously the Expected Competitive Customer Return for Investor (ECRI), Non Performing Financing (NPF)) and Bank Indonesia Rate (BI Rate) have not significantly affected the margin of murabahah revenue at BMT Al Ghazaly refers to its yearly financial report during the years of 2012 up to 2016. Partially ECRI has not significantly affected the margin of murabahah revenue. Nevertheless, at the same condition, partial NPF has not significantly affected the margin of murabahah revenue. As well as partial BI rate has not significantly affected the margin of murabahah revenue.Keywords: ECRI, NPF, BI Rate, Margin Revenue, Murabahah